Kelaikan Manhaj Al-Zarnujiy dalam Membangun Mental-Spritual Generasi Millennial dan Zoomer - Sunardi Bashri Iman; Ahmad Falhan; Achmad Yaman (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
AbstractThe fundamental problems faced by generations M and Z are mental-spiritual health, such as not upholding the ethics of politeness, individualism, and lack of interest in reading conventionally. The purpose of this study is to offer mental-spiritual therapy for them in accordance with the manhaj of Al-Zarnujiy in his book Ta'limul Muta'allim. This qualitative study uses a descriptive analysis approach to find the answer: What is the reason that the manhaj of Al-Zarnujiy is still considered qualified to build the mental-spiritual of the millennial and zoomer generations? The researcher believes that the Al-Zarnujiy method is still very suitable for them to apply for the first reason: The originality of the method, second: full of motivation and inspiration in the method, and third: prioritizing anticipatory actions to the maximum to minimize failure.